Design of Nutrition Automation on Lactuca Sativa NFT Hydroponic Systems - Joko Slamet Saputro; Ulinnuha Latifa; Agus Ramelan (Journal of Electrical, Electronic, Information, and Communication Technology, 2020)
This research focus on preserved nutrition on lettuce plants, as well as automation of other parameters that affect plant growth in NFT type hydroponic systems such as temperature, water acidity (pH), water level and light intensity. The automation of this hydroponic system includes the provision of nutrients according to the needs of plants by utilizing EC sensors, keeping the temperature of the water in accordance with plant specifications as well as water levels that are maintained.